O carnaval e o mundo burguês - Brito, Sandra (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present article intends, through a historic-social boarding of the Carnival celebration in the end of the 20th century and the beginning of the 20th century, to apprehend it’s inherent the social directions, on behalf to understand the alliances and conflicts that characterize the social relations that served to it of base, as well as all the process of reorganization of this Celebration of the “Momo”, that then occurred in the Porto city. We look for, also, to understand of that it forms and under that arguments the Porto’s bourgeoisie reorganized this celebration, placing it its service structuralizing it in accordance with the two main pillars of the bourgeois society: the profit and the power.